Control of crystalline characteristics of shell in core-shell magnetoelectric nanoparticles studied using HRTEM and holography. (20th October 2016) - Betal, Soutik; Dutta, Moumita; Cotica, Luiz F.; Bhalla, Amar S.; Guo, Ruyan
ABSTRACT: Magnetoelectric layered composites can be designed to exhibit the magnetoelectric effect based on transfer of stress from magnetostriction of ferromagnetic layer to the ferroelectric layer. In this study Core-Shell magnetoelectric nanoparticles (CSMEN) have been fabricated by coating BaTiO3 on CoFe2 O4 nanoparticles (∼50nm) by molar mass ratio using hydro-thermal method. The control factor in the fabrication process is the use of different shape and morphology of the CoFe2 O4 core. The crystallinity of the barium titanate (BT) coating changes from single crystalline to polycrystalline nature depending on the BT coating thickness. The BT shell thickness during CSMEN fabrication largely varies with the morphology of the substrate which is the cobalt ferrite nanoparticle. The shape, size and coagulation are the morphological characteristics of cobalt ferrite nanoparticles which plays major role for single crystalline BT coating on it. The bigger the size or the uneven surface morphology/shape of cobalt ferrite nanoparticles, the bigger (polycrystalline) BT shells formation by the same process of fabrication. The process of coating of BT shell on cobalt ferrite nanoparticles is analyzed step by step to accurately measure the maximum thickness of shell to sustain single crystallinity. The maximum size of BT coating prepared by this method to sustain single crystallinity is up to 41.2 nm which is approximately ∼100 unit cells of barium titanate. High resolution transmission electron microscopy (HRTEM), selected area electron diffraction pattern (SAED) and holography have been used in this study to visualize and characterize the integrated morphology of CSMEN.